2019
DOI: 10.1016/j.chom.2019.09.014
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Pathogen Type III Effector Protein Subverts Translational Regulation to Boost Host Polyamine Levels

Abstract: Highlights d A Ralstonia solanacearum TALE activates host ADC genes d Due to a truncated 5 0 UTR, the TALE-induced ADC mRNA subverts translational control d ADCs inhibit in planta growth of Pseudomonas syringae but not of R. solanacearum d Brg11-induced responses possibly aid R. solanacearum by hindering niche competitors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 65 publications
2
78
0
Order By: Relevance
“…In the context of plant-pathogen co-evolution, the polyamine pathway might be a good target for pathogen effectors or small molecules which are delivered to manipulate host defenses. The observed restriction in Pseudomonas growth triggered by Put is consistent with the activity of the TALE-like Bgr11 effector from the plant pathogen Ralstonia solanacearum that boost Put biosynthesis to inhibit the growth of microbial niche competitors (Wu et al, 2019). In addition, the P. syringae virulence factor phevamine A, which is derived from Spd, suppresses the flg22-induced ROS potentiation of defense responses triggered by Spd in Arabidopsis (O'Neill et al, 2018).…”
Section: Discussionsupporting
confidence: 65%
“…In the context of plant-pathogen co-evolution, the polyamine pathway might be a good target for pathogen effectors or small molecules which are delivered to manipulate host defenses. The observed restriction in Pseudomonas growth triggered by Put is consistent with the activity of the TALE-like Bgr11 effector from the plant pathogen Ralstonia solanacearum that boost Put biosynthesis to inhibit the growth of microbial niche competitors (Wu et al, 2019). In addition, the P. syringae virulence factor phevamine A, which is derived from Spd, suppresses the flg22-induced ROS potentiation of defense responses triggered by Spd in Arabidopsis (O'Neill et al, 2018).…”
Section: Discussionsupporting
confidence: 65%
“…transcription activator‐like (TAL) effectors (de Lange et al ., 2013). RipTAL induces the expression of plant genes involved in the synthesis of polyamines, evading their native translational regulation mechanisms (Wu et al ., 2019). It is hypothesized that this RipTAL‐induced boost of the plant polyamine levels prevents the proliferation of possible Ralstonia competitors (Wu et al ., 2019).…”
Section: Many T3es But For What Purpose?mentioning
confidence: 99%
“…A recent study by Peng et al [82] reported that Tal8 from Xtu target and induce the expression of host gene Ta-NCED-5BS, encode enzyme required for rate-limiting step in ABA biosynthesis, to promote disease susceptibility. In another new study, Wu et al [83] shown that TAL-effector Brg11 from Ralstonia solanacearum enhance the expression of 5-truncated ADC (arginine decarboxylase) transcripts that subvert translational control and thereby inhibit competing pathogens. In Xcm, Avrb6 was the first TALE shown to be important for virulence [25].…”
Section: Discussionmentioning
confidence: 99%